Lecturers and Students’ Perception and Practices of Students’ Presentation to Enhance Their Speaking Skills - Saritwa, Firdausi Wimad; Fitriani, Sri Wuli; Faridi, Abdurrachman (Universitas Negeri Semarang, 2018)
This study aimed to explain: (1) the perceptions of English lecturers of UIN Walisongo Semarang towards students’ presentation in enhancing students’ speaking skills, (2) the perceptions of English department students of UIN Walisongo Semarang towards students’ presentation in enhancing students’ speaking skills, (3) the classroom practices of students’ presentation in learning English at UIN Walisongo Semarang, (4) the implementation of students’ presentation in helping students to enhance their speaking skills. This study is a classroom discourse analysis which employs a descriptive qualitative approach. In order to collect the data, the researcher used personal interview, classroom observation, and open questionnaire. This study presents that: (1) the English lecturers of UIN Walisongo Semarang have good perception towards the students’ presentation in enhancing the students’ speaking skills. (2) the English department students of UIN Walisongo Semarang have good perception towards the students’ presentation in enhancing the students’ speaking skills, only some students who have negative perception. (3) there are three main stages of classroom practices of students’ presentation in learning English at UIN Walisongo Semarang. Those are the presentation itself, question and answer session, and the last is getting feedback from the lecturers. (4) students’ presentation brings benefits for students in helping them to enhance their speaking skills. Students are motivated to speak actively, and it encouraged them to achieve the grammatical competence, sociolinguistic competence, discourse competence, and strategic competence.